Modern evaluation instruments in education - Alarilla, Luis M. (Education quarterly.)
Anecdotal reports or ratings, interview, questionnaire, rating device, sociometric technique, and cumulative record are some of the instruments used in modern evaluation in education. Proper use plus a good knowledge of the statistical procedures in the interpretation of their results would mean systematic guidance and an excellent follow-up of the educational progress of every student in our educational system.